Reporturile dintre Psihologie si Diplomatie. - Galindo, Edgar (2016)
An analyisis of the diplomatic work and the contribution of Psychology for understanding his problems and achieving his tasks. Análisis del quehacer el diplomático y de la contribución de la psicología para comprender sus problemas y realizar sus tareas.